Deployment of attention to facial expressions varies as a function of emotional quality—but not in alexithymic individuals - Surber, Chiara; Hoepfel, Dennis; Günther, Vivien; Kersting, Anette; Rufer, Michael; Suslow, Thomas; Bodenschatz, Charlott Maria (Frontiers in Psychiatry, 2024)
Background: Alexithymia is a risk factor for emotional disorders and characterized by differences in automatic and controlled emotion processing. The multi-stimulus free-viewing task has been used to detect increased negative and reduced positive attentional biases in depression and anxiety. In the present eye-tracking study, we examined whether lexical emotional priming directs attention towards emotion-congruent facial expressions and whether alexithymia is related to impairments in lexical priming and spontaneous attention deployment during multiple face perception. Materials and Methods: A free-viewing task with happy, fearful, angry, and neutral faces shown simultaneously was administered to 32 alexithymic and 46 non-alexithymic individuals along with measures of negative affect and intelligence. Face presentation was preceded by masked emotion words. Indices of initial orienting and maintenance of attention were analyzed as a function of prime and target category and study group. Results: Time to first fixation was not affected by prime category or study group. Analysis of fixation duration yielded a three-way interaction. Alexithymic individuals exhibited no prime or target category effect, whereas non-alexithymic individuals showed a main effect of target condition, fixating happy faces longer than neutral and angry faces, and fearful faces longer than angry faces. Discussion: Our results show evidence of attentional biases for positive and fearful social information in non-alexithymic but not in alexithymic individuals. Lack of spontaneous attentional preference for these social stimuli in alexithymia might contribute to a vulnerability for developing emotional disorders. Our data suggest also that briefly presented emotion words may not facilitate gaze orientation towards emotion-congruent stimuli.